Injury incidence in Japanese elite junior divers - Narita, T.; Kaneoka, K.; Takemura, M.; Nomura, T.; Sakata, K.; Miyakawa, S. (Japanese Journal of Sciences in Swimming and Water Exercise, 2011)
In competitive diving, divers jump up from 1 or 3 m springboards or 5-10 m platforms and dive into the water. At the time of water entry, the force of impact is very large, which places tremendous physical stress on the diver. However, there are few investigations about injury occurrence in divers, especially during the junior period. Thus, this study aimed to describe the prevalence of injuries among elite junior divers over a 7-year period. One hundred and sixteen (60 male, 56 female) Japanese elite junior divers were included in this study. Parts of pain and injury incidence scene that the divers experienced were assessed by questionnaires during national training camps. Low back pain(LBP)was assessed by interviews, and physical examinations. The major findings were as follows: (1) Among all types of injuries, there was high prevalence of LBP (38.4%) in elite junior divers in Japan. (2) Most injuries occurred at the time of water entry.